Foot‐and‐mouth disease virus detection on a handheld real‐time polymerase chain reaction platform. Issue 4 (5th June 2019) - Hole, Kate; Nfon, Charles
Abstract: Foot‐and‐mouth disease (FMD) is a highly contagious disease of livestock that requires rapid control. Early detection is critical but transportation of samples to laboratory delays testing. Sensitive and specific field‐deployable assays are therefore desirable. Real‐time reverse transcription polymerase chain reaction (RRT‐PCR) and RRT‐loop‐mediated isothermal amplification assays for FMDV on portable platforms have been described but none of these are handheld. In this report, we have evaluated a handheld Biomeme two3™ Real‐Time PCR Thermocycler (two3) as a field‐deployable platform for FMDV RRT‐PCR targeting the 3D gene segment. Two3's performance was compared with the laboratory‐based reference assay on the ABI7500 platform. RNA extraction using a rapid Biomeme proprietary sample prep technology (M1) was compared with MagMax RNA extraction. Two3 successfully detected FMDV isolates for six serotypes (O, A, Asia 1, SAT 1, 2 and 3). Serotype C was excluded since it has not been detected in the field since 2004. The limits of detection for serial 10‐fold dilutions of cell culture isolates were equal or one log different between two3 and ABI7500. Furthermore, two3 detected FMDV RNA in multiple sample types including serum, vesicular fluid, tissue suspensions, oral fluid, oral and nasal swabs. Two3 also detected FMDV RNA directly in vesicular fluid and other samples without prior RNA extraction. Comparison of the time to first detection of a positive result in serial samples in MagMax RNA extraction/ABI7500 (MgMx/ABI) system vs. M1 RNA extraction/Two3 system revealed similar or slightly better analytical sensitivity for the MgMx/ABI system. Overall, RNA extraction by M1 yielded good results and FMDV RNA detection on two3 was not significantly different from the ABI7500. Therefore, two3 could potentially enable sensitive penside detection of FMDV within an hour using M1‐extracted RNA or direct testing of vesicular fluid and swabs without RNA extraction thereby ensuring prompt implementation of appropriate control measures.